Changes in beverage purchases following the announcement and implementation of South Africa's Health Promotion Levy: an observational study. Issue 4 (April 2021) - Stacey, Nicholas; Edoka, Ijeoma; Hofman, Karen; Swart, Elizabeth C; Popkin, Barry; Ng, Shu Wen
Summary: Background: In 2016, South Africa announced an intention to levy a tax on sugar-sweetened beverages (SSBs). In 2018, the country implemented an SSB tax of approximately 10%, known as the Health Promotion Levy (HPL). We aimed to assess changes in the purchases of beverages before and after the HPL announcement and implementation. Methods: We used Kantar Europanel data on monthly household purchases between January, 2014, and March, 2019, among a sample of South African households (n=113 653 household-month observations) from all nine provinces to obtain per-capita sugar, calories, and volume from taxable and non-taxable beverages purchased before and after the HPL announcement and implementation. We describe survey-weighted means for each period, and regression-controlled predictions of outcomes and counterfactuals based on pre-HPL announcement trends, with bootstrapped 95% CIs, and stratify results by socioeconomic status. Findings: Mean sugar from taxable beverage purchases fell from 16·25 g/capita per day (95% CI 15·80–16·70) to 14·26 (13·85–14·67) from the pre-HPL announcement to post-announcement period, and then to 10·63 g/capita per day (10·22–11·04) in the year after implementation. Mean volumes of taxable beverage purchases fell from 518·99 mL/capita per day (506·90–531·08) to 492·16 (481·28–503·04) from pre-announcement to post announcement, and then to 443·39 mL/capita per day (430·10–456·56) after implementation. Across these time periods, there was a small increase in the purchases of non-taxable beverages, from 283·45 mL/capita per day (273·34–293·56) pre-announcement to 312·94 (296·29–329·29) post implementation. When compared with pre-announcement counterfactual trends, reductions in taxable beverage purchase outcomes were significantly larger than the unadjusted survey-weighted observed reductions. Households with lower socioeconomic status purchased larger amounts of taxable beverages in the pre-announcement period than did households with higher socioeconomic status, but demonstrated bigger reductions after the tax was implemented. Interpretation: The announcement and introduction of South Africa's HPL were followed by reductions in the sugar, calories, and volume of beverage purchases. Funding: Bloomberg Philanthropies, International Development Research Centre, South African Medical Research Council, and the US National Institutes of Health.